Exploring Tourism Opportunities: Role of Financial Institutions in the Promotion of Tourism Entrepreneurship in Kerala - Ibrahim P. A. (ASEAN Journal on Hospitality and Tourism, 2021)
This study aims to assess the role of financial institutions in promoting tourismentrepreneurship in the state of Kerala; Kerala is a brand of Indian tourism and the destinyof world tourism. The study highlights the acumen behind the promotion of tourismentrepreneurship, tourism opportunities in Kerala and identifies the role of financialinstitutions in exploring tourism opportunities with the primary data sourced from 222tourism entrepreneurs of Kerala. The study found that financial institutions significantlyassist tourism enterprises in asset creation. Further, the findings reveal a positiveassociation between financial assistance in the innovation of recreation facilities and astimulus to start enterprises in the tourism sector. The study provides deeper insights tomanagers and academicians that the financial institutions should extend credit to thetourism industry as Priority Sector Lending (PSL) along with other prime lending sectors.